Faktor- faktor yang Berhubungan dengan Kadar 25 Hidroksi Vitamin D Serum pada Anak dengan Lupus Eritematosus Sistemik - wibawa, Valerie viola; Takumansang, Raynald O; Mandei, Jose M; Langi, Fima Lanra Fredrik Gerarld (Jurnal Kedokteran Meditek, 2025)
Introduction: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease affecting multiple organ systems. Pediatric-onset SLE (pSLE) often presents with more severe organ involvement and a more aggressive course than adult-onset cases. Vitamin D, known for its immunomodulatory effects, has been implicated in SLE pathogenesis, yet data on serum 25-hydroxy vitamin D [25(OH)D] levels in pediatric patients remain limited. Objective:  This study aimed to assess serum 25(OH)D levels in children with SLE and identify related factors. Methods: A cross-sectional observational study was conducted on 22 pediatric SLE patients aged 5–18 years treated at Prof. Dr. R. D. Kandou General Hospital, Manado. Patients with chronic kidney disease, nephrotic syndrome, chronic liver disease, congenital skeletal disorders, or parathyroid dysfunction were excluded. Serum 25(OH)D levels were measured via ELISA, along with other laboratory parameters. Results: Results showed all patients had vitamin D deficiency, with a mean level of 11.93 ± 5.25 ng/mL. Multivariate regression analysis revealed significant associations between vitamin D levels and complement C3, disease duration, SLEDAI scores, and dsDNA levels.  Conclusion: Vitamin D deficiency is prominent among pSLE patients and is linked to disease activity and severity, suggesting its potential role in disease management and the need for further research